2005
DOI: 10.1007/s00296-005-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of modern marker proteins in serum and synovial fluid in patients with advanced osteoarthrosis and rheumatoid arthritis

Abstract: Numerous studies have focused on the significance of modern marker proteins in the synovial fluid of the knee joint and in the serum both, for osteoarthritis (OA) and rheumatoid arthritis (RA). The relationship between the serum concentrations and the concentrations in the synovial fluid is still unclear. Synovial fluid and serum samples were obtained from 13 patients with advanced OA and from 8 patients with severe RA and concentrations of MMP-1, MMP-3, MMP-13, TIMP-1, COMP and MIA/CD-RAP were determined. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…Similar results were found by El-Arman et al, 21 Gheita et al, 22 and Andereya et al, 23 suggesting that COMP is produced in the joint and associated Some studies have concluded that serum COMP levels vary between sexes and among different ethnicities. 6,24 Indeed, COMP levels may vary in biologic fluids, due to several factors.…”
Section: Discussionsupporting
confidence: 79%
“…Similar results were found by El-Arman et al, 21 Gheita et al, 22 and Andereya et al, 23 suggesting that COMP is produced in the joint and associated Some studies have concluded that serum COMP levels vary between sexes and among different ethnicities. 6,24 Indeed, COMP levels may vary in biologic fluids, due to several factors.…”
Section: Discussionsupporting
confidence: 79%
“…Also, it has been used as a marker for the induction state in inflammation, including auto-immune diseases, cancer [20], and intra-amniotic infection [23]. MMP-13 has also been evaluated as a potential marker to monitor the cause of arthritis [24] and cancer [25]. MMPs may be a useful marker of pathological conditions in Japanese flounder as these enzymes up-regulated in the course of E. tarda infection.…”
Section: Identification Of Differentially Expressed Genes and Evaluatmentioning
confidence: 99%
“…We were unable to detect MMP-13 in any of the 259 RA serum samples tested, and other investigators detected MMP-13 in only 9 of 56 RA sera (14). In studies of patients with juvenile idiopathic arthritis, MMP-13 was also undetectable in serum and synovial fluid (26), while other authors have detected MMP-13 in the serum of patients with osteoarthritis (27,28). It has been suggested that levels of MMP-13 in RA patients may be low due to active removal and degradation by chondrocytes and synoviocytes via a specific surface MMP-13 receptor (29)(30)(31).…”
Section: Young-min Et Almentioning
confidence: 99%